Effect of Three Different Centrifugation on Cryosurvival of Goat Spermatozoa Supplemented with Vitamin E - Ezekiel ADEKUNLE; Adebisi ODEYEMI; Bukola MAJEKODUNMI; Oluwaseun AKOSILE; Obafemi AKINJUTE; James DARAMOLA; Okanlawon ONAGBESAN; Olusiji SOWANDE (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca. Animal Science and Biotechnologies)
Three different centrifugation frequencies viz., zero time (ZTC), one time (ITW), two times (2TC) and three times (3TC) supplemented with different levels of vitamin E were studied under in vitro cryosurvival of West African Dwarf (WAD) goat spermatozoa. Semen samples were washed ITW, 2TC and 3TC and supplemented each with 2, 4, 6 and 8 mM of vitamin E in a 3x4 factorial arrangements and cryopreserved for 30 days in liquid nitrogen. Data were subjected to one-way ANOVA. Spermatozoa cryopreserved with Tris-based extender supplemented with 6 and 8 mM using 3TC and 8 mM with 2TC had highest (P<0.05) percentage motility, percentage acrosome integrity and percentage live spermatozoa while highest (P<0.05) percentage membrane integrity were observed at 4, 6 and 8 mM. Cryopreserved spermatozoa with 6 and 8 mM for 3TC had the lowest (P<0.05) percentage abnormality and highest (P<0.05) percentage spermatozoa that underwent acrosome reaction including 8 mM using 2TC. Also 4, 6 and 8 mM for 3TC and 6 and 8 mM using 2TC had the highest (P<0.05) percentage spermatozoa that underwent capacitation. The results showed lowest (P < 0.05) concentrations of Malondialdehyde MDA at 2, 4, 6 and 8 mM for 1TC, 6 and 8 mM for 2TC and ZTC; and 8 mM vitamin E for 3TC. However, the Tris extenders supplemented with 2 and 4 mM for ZTC and 4 mM for 1TC had highest (P<0.05) values for arginase activity. Cryopreservation of WAD goat buck sperm with 2TC and 3TC improved viability and fertilizing ability.